Gasdynamical flows in star forming regions - Yeghikyan, A. G.
A review of gas-dynamical flows in astrophysics is given with an emphasis on accretion flows and outflows. Analytical estimates of the dependence of the velocity and density on the radius during spherical accretion are considered, as well as the rate of mass inflow and the corresponding luminosity of the accretion disk are also estimated. Some features of gas inflow and outflow near the star are mentioned, like mass-loading flows where source functions of mass and momentum are presented and analyzed. The velocities and radii of the ionization fronts of hot stars are considered. The Sedov-Taylor analytical formula on the dependence of the radius of the fireball on time during a strong explosion is given, where the explosion energy and density of the medium act as parameters. Examples of the use of dimensional theory in astrophysics, in particular, in accretion flows used above are considered. An example of a numerical solution of the interaction of an interstellar cloud with the solar wind is also given, followed by an estimate of the inflow of the cloud’s gas environment into the Earth’s atmosphere, which affects the terrestrial ozone content.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture